The rights of official language minority communities in Canada - Eastaugh, É (2015)
This thesis explores the meaning and content of s. 41 of the Official Languages Act of Canada, which imposes certain duties on all federal institutions towards French- and English-language minority communities. While vitally important as a component of Canada’s language rights archictecture, the nature and content of s. 41 as a legal norm remain woefully unclear. The immediate aim is to determine: (1) whether s. 41 confers a right to specific measures in particular cases; (2) whether such rights are individual or collective; and (3) if collective, what sort of interests are protected. Section 41 presents a number of interpretive challenges. First, it uses terminology which is undefined in the Act and yet has no self-evident meaning. Thus, the nature of the primary legal subject, 'linguistic minority communities' (LMCs), is unclear, as are the nature of the protected interests, 'vitality' and 'development'. Second, the interpretive principles developed by the case-law for official language rights rely on a conceptual framework that is vague and under-theorized. Key components of that framework, like the concept of a necessary link between language and culture, have yet to be fully explored, either in the case-law or in legal scholarship. This presents an acute problem in the case of s. 41, where the content of these concepts will likely prove dispositive. In order to grapple with these challenges, this thesis develops an account of language rights as collective rights. Drawing on the philosophical literature and existing case-law, I argue that LMCs should be conceived of as collectivities rather than mere aggregates of individuals, and that a number of language rights, such as s. 41 of the OLA, and ss. 16.1 and 23 of the Charter, aim to protect the collective interests of these collectivities. I then define some of these interests from both an empirical and a normative perspective. I conclude by arguing that s. 41 of the OLA protects an 'autonomy interest', which both prohibits federal institutions from interfering with existing LMC autonomy, and provides a basis for claiming enhancements to that autonomy, within the confines of the statutory mandate of the institution in question.